REPENSANDO AS FRONTEIRAS: A TRADUÇÃO DE IDENTIDADES NA OBRA DE JORGE LUIS BORGES - de Oliveira, Denise Vallerius (Organon, 2004)
The rearrangement of concepts about frontiers has made possible the emergence of a different approachto Jorge Luis Borges’ regionalist production – this production has often been misunderstood and supposedlyconsidered inappropriate in relation to his other universal and remarkable masterpieces. However, the themefrontiers is set up within the limits of his pampa i revealing the need to search for identities that insist on denyingtheir own proper definition. It demands different representations: first, the frontier between the country and the city,in the shade of Sarmiento and Hernández – the former, desiring a civilized and urbane Argentinean identity, totallyagainst the country barbarian; the latter, speaking of the pampa and the gaúchoii as if in a free existence, opposite tothe urbanized world. After these descriptions of city and country, Borges proposes to talk about the “arrabal”region, which translates a certain meaning of frontier, delineated by “fights and guitars” between the pampa andBuenos Aires. Once this new frontier is established, he tries to write about the ambiguous human being who lives inthat region: the compadrito – a mix of the urban man and the gaucho. This compadrito belongs to a place whichcannot be completely delimitated; he is intended to be not only a representation of Argentina’s culturecharacteristics, once his identity is often migrating between the I and the Other, thus making possible the listening tothe voices of differences, therefore translating this frontier identity – the one that truly represents the very Latin-American self.